P I organises briefing on UMP Research Fund Grants - Idayu, Mat Ali; Nur Hartini, Mohd Hatta (2021)
PEKAN, 20 October 2021 - The Research and Innovation Department organised an online briefing session on Universiti Malaysia Pahang (UMP) Research Fund Grants through Microsoft Teams to provide the latest inputs related to improving guidelines for UMP research grants.